miR-223: An Immune Regulator in Infectious Disorders - Yuan, Shun; Wu, Qi; Wang, Zhiwei; Che, Yanjia; Zheng, Sihao; Chen, Yuanyang; Zhong, Xiaohan; Shi, Feng (Frontiers in Immunology, 2021)
MicroRNAs (miRNAs) are diminutive noncoding RNAs that can influence disease development and progression by post-transcriptionally regulating gene expression. The anti-inflammatory miRNA, miR-223, was first identified as a regulator of myelopoietic differentiation in 2003. This miR-223 exhibits multiple regulatory functions in the immune response, and abnormal expression of miR-223 is shown to be associated with multiple infectious diseases, including viral hepatitis, human immunodeficiency virus type 1 (HIV-1), and tuberculosis (TB) by influencing neutrophil infiltration, macrophage function, dendritic cell (DC) maturation and inflammasome activation. This review summarizes the current understanding of miR-223 physiopathology and highlights the molecular mechanism by which miR-223 regulates immune responses to infectious diseases and how it may be targeted for diagnosis and treatment.